2015
DOI: 10.1161/hypertensionaha.115.05925
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal and Secular Trends in Blood Pressure Among Women and Men in Birth Cohorts Born Between 1905 and 1977

Abstract: High blood pressure is a modifiable risk factor for cardiovascular disease. Previous studies showing a blood pressure decline in recent decades lack data to follow individuals born in different decades from early and middle adulthood to older age. We investigated changes in age-specific blood pressure by repeated measurements in 37973 women and men born 1905 to 1977 (aged 20–89 years) examined ≤5× between 1979 and 2008 in the population-based Tromsø Study. Mixed models were used to estimate time trends. Mean s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
31
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 21 publications
9
31
1
Order By: Relevance
“…The results suggested that there was an increase in awareness, treatment and control of hypertension from 1988 to 2010 [32]. Our results showing a decrease in both SBP and DBP in the untreated group are consistent with the findings from the Tromsø study, which showed a trend of BP reduction in the entire population, suggesting a whole population change potentially related to factors other than treatment [31]. …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results suggested that there was an increase in awareness, treatment and control of hypertension from 1988 to 2010 [32]. Our results showing a decrease in both SBP and DBP in the untreated group are consistent with the findings from the Tromsø study, which showed a trend of BP reduction in the entire population, suggesting a whole population change potentially related to factors other than treatment [31]. …”
Section: Discussionsupporting
confidence: 87%
“…In the Tromso study, SBP in middle age decreased by 10.6 mmHg in women and 4.5 mmHg in men between 1979 and 2008. They suggested that this was mainly due to improved life style factors such as a reduction in smoking and salt intake and an improvement in diet [31]. The present report reveals comparable decreases in SBP and DBP but shows that changes are broadly similar in men and women, in participants treated for hypertension as well as those not, and in subgroups of age over 80 years.…”
Section: Discussionsupporting
confidence: 62%
“…[8][9][10] CVD risk factors found to be associated with aging-related phenotypes in cross-sectional analyses can differ from observed associations in longitudinal analyses.…”
mentioning
confidence: 84%
“…In Norway and several other Western countries, average blood pressure has declined since the 1980s (49,50), even in those who use no antihypertensive drugs and in spite of weight gain. The reason is unknown, but a reduced intake of salt and an increased intake of fruits and vegetables, which contain a lot of potassium, may be of importance -and line with the findings in this review article.…”
Section: Discussionmentioning
confidence: 99%